2007
DOI: 10.1124/jpet.106.117010
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin, a Citrus Flavonoid, Reverses Learning Impairment Associated withN-Methyl-D-aspartate Receptor Antagonism by Activation of Extracellular Signal-Regulated Kinase Signaling

Abstract: Recent studies have indicated that learning-induced activation of extracellular signal-regulated kinase (ERK) signaling via Nmethyl-D-aspartate (NMDA) receptors is required for consolidation of the resultant learning. These findings raise an idea that control of ERK signaling may be a potential target for treatment of cognitive dysfunction. Our recent studies have demonstrated that nobiletin, a polymethoxylated flavone from Citrus depressa, enhances cAMP/protein kinase A/ERK signaling in cultured rat hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
43
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 39 publications
2
43
0
Order By: Relevance
“…On the other hand, there are a number of reports concerning a variety of biological effects of tangeretin and nobiletin, especially nobiletin, in addition to the concentrations of polymethoxy flavones in various species of citrus (10,11). For instances, direct and indirect evidences have been provided for anti-cancer effects (12)(13)(14)(15)(16)(17)(18)(19)(20), anti-inflammatory effects (21)(22)(23)(24), inhibition of NO production (25,26), enhancement of differentiation and lipolysis of adipocytes (27), prevention of cartilage destruction (28), improvement of memory impairment (29) and neurodegradation (30). However, no liver injury-suppressive effect of tangeretin and nobiletin has been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are a number of reports concerning a variety of biological effects of tangeretin and nobiletin, especially nobiletin, in addition to the concentrations of polymethoxy flavones in various species of citrus (10,11). For instances, direct and indirect evidences have been provided for anti-cancer effects (12)(13)(14)(15)(16)(17)(18)(19)(20), anti-inflammatory effects (21)(22)(23)(24), inhibition of NO production (25,26), enhancement of differentiation and lipolysis of adipocytes (27), prevention of cartilage destruction (28), improvement of memory impairment (29) and neurodegradation (30). However, no liver injury-suppressive effect of tangeretin and nobiletin has been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…43) Nobiletin rescued impaired memory in olfactory-bulbectomized mice accompanied by cholinergic neurodegeneration and reversed olfactory bulbectomy-induced reduction of acetylcholinesterase and choline acetyltransferase. 22) Nobiletin improved learning and memory impairment in several brain disease models, such as a N-ethyl-D-aspartate receptor antagonism model, 44) an ischemia animal model with bilateral common carotid artery occlusion (BCCAO), 24) and an amyloid precursor protein (APP) transgenic mouse model which over expresses human APP 695 harboring the double Swedish and London mutation.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that nobiletin activates an extracellular signal-regulated kinase (ERK) / mitogen-activated protein kinase (MAPK)-dependent signaling pathway to trigger CREB phosphorylation and CRE-dependent transcription in cultured hippocampal neurons and PC12D cells (6,7). In addition, nobiletin reverses learning impairment associated with N-methyl-D-aspartate (NMDA)-receptor antagonism by activation of ERK signaling in the hippocampus of mice (14). A number of studies have shown that the CREB / CREdependent transcription pathway regulates the expression of genes involved in synapse formation, neuronal survival (BDNF, BCl-2), and long-term memory formation (C / EBP) (10).…”
mentioning
confidence: 99%